PENGARUH WAKTU, SUHU UDARA DAN KELEMBABAN UDARA TERHADAP HASIL PEMERIKSAAN CAIRAN MANI DAN SPERMATOZOA PADA KAIN POLYESTER - Muhammad Arif Kurniawan; Mohammad Tegar Indrayana; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The finding of the presence of seminal fluid and sperm was the gold standard of the examination from victim of sexual crimes. A total from 75.6% of victims of sexual crimes were late to report to the authorities. The influence of air temperature, humidity, CO2 and sunlight exposure directly to the spermatozoa were the occurrence of DNA’s fragmentation. DNA’s fragmentation causes disruption of the bond between the DNA and acid fushsin, so the sperm’s morphology could not be seen with the test Baechi. Air temperature and air humidity were not affect to spermine picric. This study is a descriptive research and experimental design in to knew the influence of time, air temperature, air humidity on the results of seminal fluid and spermatozoa’s examination. This study uses Barberio test for the identification of seminal fluid and sperm test Baechi for identification. The results of this study was still finding spermatozoa with Baechi test for ten days and still finding semen with Barberio test for fifteen days.Key words : semen fluid, spermatozoa,time, air temperature and air humidity.